A Uterus‐Inspired Niche Drives Blastocyst Development to the Early Organogenesis (Adv. Sci. 28/2022). Issue 28 (5th October 2022) - Gu, Zhen; Guo, Jia; Zhai, Jinglei; Feng, Guihai; Wang, Xianning; Gao, Zili; Li, Kai; Ji, Shen; Wang, Leyun; Xu, Yanhong; Chen, Xi; Wang, Yiming; et al.
Abstract : Early Organogenesis In vitro culture of embryos is a useful tool to explore the mysteries of life. As the natural platform for embryo development, the uterus inspires the building of in vitro culture conditions. In article number 2202282 by Qi Gu, Hongmei Wang, Shutao Wang, and co‐workers, particularly designed collagen is grafted onto polydimethylsiloxane to simulate the moduli of the endometrium and uterine horn and the microstructure of the endometrium during mouse pregnancy. The uterus‐inspired niche microenvironment controls the migration and assembly of extraembryonic tissues, simulates embryo implantation, and ultimately promotes embryo development to early organogenesis.